The Correlation between Students’ Metacognitive Reading Strategies and Reading Comprehension - Putri Salsyabillah.M; Sulastri Manurung; Adam Adam (Didaktika: Jurnal Kependidikan, 2025)
Reading comprehension is an essential skill for academic success, particularly for students developing literacy through reading. Nevertheless, lack of awareness or ineffective reading strategies frequently lead to students encountering challenges in understanding texts. Metacognitive strategies have been considered important means to improve students’ Reading comprehension. This study aims to analyze the relationship between metacognitive reading strategies and reading comprehension using a quantitative approach with a correlational design. The study employed the Survey of Reading Strategies (SORS) developed by Mokhtari to measure metacognitive strategies and a reading comprehension test compiled based on language assessment theory. Data were collected from 98 students at a Vocational School in Batam, Kepulauan Riau, Indonesia. The Spearman Rho non-parametric correlation method was used to analyze the data. The findings imply no statistically significant relationship exists between metacognitive reading strategies and students' reading comprehension. This study provides important insights into the effectiveness of learning strategies in educational contexts. Therefore, it is recommended that further research be conducted to investigate other factors that may contribute to reading comprehension and evaluate more comprehensive learning approaches in improving students' reading skills. The practical implication of this study is the importance of integrating metacognitive strategies in reading learning to enhance students' learning outcomes.